PENDEKATAN PEMURIDAN DALAM IMPLEMENTASI PENDIDIKAN AGAMA KRISTEN DI PERGURUAN TINGGI: The Discipleship Approach to Implementation of Christian Religious Education in Higher Education - siby, lenardus (STT INDONESIA MANADO, 2021)
This article highlights the implementation of Christian Religious Education (PAK) in Higher Education. The implementation of PAK, is a mandate of the law in force in Indonesia. This is of course a form of protection and guarantee from the state for the implementation of PAK in higher education. However, the implementation of PAK requires a new approach and point of view, so that its implementation does not become a formal teaching system. This article was written using a literature study approach with a descriptive method. This is done by examining the laws that underlie the implementation of religious education in higher education, as well as describing the learning content. From the results of the study it was found that the implementation of PAK in higher education was directed at the concept of discipleship. So that the implementation of PAK in Higher Education is not only limited to fulfilling SKS but is interpreted and carried out in the spirit of an encounter with Christ, as well as a commitment to live in faith in Christ, as the basis for transforming life both personally and in the context of social life in Indonesia